Pengaruh Motivasi Belajar dan Ajaran Tri Juang terhadap Perilaku Kecurangan Akademik Mahasiswa Akuntansi - Wardani, Dewi Kusuma; Simbolon, Rica Hanaria (STAI Auliaurrasyidin Tembilahan, 2024)
This study aims to obtain evidence about the influence of learning motivation and the Tri Juang Teachings on academic fraud behavior in Tamansiswa University Bachelor's students of accounting department. This research method uses a quantitative descriptive method and primary data collected using a questionnaire. This study used a sample of active students at accounting department in the Sarjanawiyata Tamansiswa University of Yogyakarta (UST). The sampling technique uses the Slovin formula. The data collection method uses a questionnaire in the form of a Google Form. The number of questionnaires processed was 100. The data were analyzed using IBM SPSS Statistics 20. The results showed that learning motivation had no effect on academic cheating behavior, and the tri-juang teachings had a negative effect on academic cheating behavior. Research can then expand this research by adding several other variables that can influence it, such as self-control, moral competence, and religiosity. This study is important to study because it has renewal, namely that it adds the variables of learning motivation and Tri Juang teachings to academic cheating behavior, two of which are variables that are still limited to study and research, so researchers are interested in studying this topic.